Ethnobotanical Effect Of Psidium Guajava L. In Glucose Control In Patients With Type 2 Diabetes Mellitus (The Review of Diabetic Studies, 2025)
Type 2 Diabetes Mellitus (DM2) is characterized by chronic hyperglycemia and metabolic disorders, resulting in costly treatments. Therefore, herbal medicine is suggested, specifically the use of Psidium Guajava L. (guava), as a sustainable alternative for prevention and treatment. This review aims to describe the parts of the plant and demonstrate their benefits to promote the consumption of its leaves in glycemic control. 532 original research articles were collected, selecting 70 where it is shown that guava leaf extract significantly contributes to the reduction of hyperglycemia, thanks to its active metabolites and mechanisms of action. In conclusion, new advances in the antidiabetic effects of guava leaf could be applied in the development of drugs, therapeutic diets, and functional foods. Further studies are recommended to demonstrate the efficacy, safety, and dosage of guava leaf extracts.